Implementation Of Management Standards For MTs An-Nur Palangka Raya In Improving Madrasah Quality - Puspita, Puspita; Ajahari, Ajahari; Misbah, Misbah; Arifin, Anwar; Asmawati, Asmawati; Tejawiani, Ida (International Journal of Educational Research & Social Sciences, 2022)
This research examines the implementation of management standards at Mts an-nur Palangkaraya in improving the quality of Madrasah education. The objectives of this study include: To find out the standard management program planning, implementation of standard management programs, monitoring and evaluation of standard management programs at MTS An- nur Palangkaraya. This research uses a qualitative descriptive approach, as Moleong argues "qualitative research is in the form of words either written or spoken from people and observed behavior" while the research location is at MTS an-Nur Palangkaraya. research purposes, this study used interviews, participant observation and documentation. The data obtained were analyzed through data reduction, data presentation, and drawing conclusions. The results of this study indicate (1) Management planning at an-nur madrasah has been carried out in accordance with government regulations and education management standards, namely starting with planning. The planning carried out by Mts Anur begins with analyzing the needs and where the direction of the madrasa will be taken in the future by formulating a vision, mission and goals. All of this is done by involving all components in the madrasa. (2) Implementation Implementation of the program begins with reviewing the KTSP curriculum, implementing teaching and learning activities, and implementing Teacher Quality Improvement at MTs Annur Palangka Raya. The implementation of improving the quality of Education Personnel is pursued by implementing a strategy of increasing the integration of improving the mental, moral and spiritual discipline of teachers, learning supervision, involving teachers in training activities, attending seminars and being active in the Palangka Raya City MGMP forum. dhuha prayer. The program to improve the quality of infrastructure at MTs Annur Palangka Raya was pursued by collaborating with the City and Provincial Ministry of Religion offices, Central Kalimantan Provincial Government, Palangka Raya City Government, Municipal and Provincial Education Offices, Collaboration with Parents of Students through Madrasah Committees, Approach with Management Foundations, Entrepreneurs, City, Provincial DPRD Members and members of the Republic of Indonesia DPR (3) Program monitoring and evaluation begins with programs developed in extra-curricular activities. This activity was carried out by developing extra-curricular activities which aim to provide opportunities for MTs Annur Palangka Raya students to develop and express themselves according to the skills and talents that students have. From the self-development program, MTs Annur students have won several achievements at the City of Palangkaraya, Central Kalimantan province, and the Province of.